Innovation Processes and Technologies for Improvement and Support of Education - Peter Balco; Martina Drahošová; Michal Greguš (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The education institutions present a complicated economic and social ecosystem with many processes that are constantly under pressure from many stakeholders. Learning organizations are trying to find ways to improve them, but they crash at "unmistakable claims" about the need to build extensive infrastructure for modernization, innovation and greater efficiency. This approach creates requirements for the maintenance and operation of complicated technologies that naturally requires additional resources, both financial and human. In our contribution, we want to present innovative approaches in processes of education based on the agile event management. The agile environment enforces to use the intelligent tools through providers, third parties, allowing automation of service management and replacing many manual activities. Automation provides two-way real-time communication that creates space for users quickly respond to different needs, events and increase productivity.
Keywords: M21; 330; education; automation; artificial intelligent; universities